Human computation - von Ahn, Luis (2009 46th ACM/IEEE Design Automation Conference, 2009)
This talk is about harnessing human brainpower to solve problems that computers cannot. Although computers have advanced dramatically over the last 50 years, they still do not possess basic conceptual intelligence or perceptual capabilities that most humans take for granted. By leveraging human abilities in a novel way, I solve large-scale computational problems and collect data to teach computers basic human talents. To this end, I treat human brains as processors in a distributed system, each performing a small part of a massive computation.